Lethal drought leads to reduction in nonstructural carbohydrates in Norway spruce tree roots but not in the canopy. (26th February 2013) - Hartmann, Henrik; Ziegler, Waldemar; Trumbore, Susan; Knapp, Alan
Summary Heat waves and droughts are expected to increase in frequency and severity in many regions with future climate change, threatening the survival of a number of forest ecosystems. However, our understanding of the physiological processes and mechanisms underlying drought‐induced tree mortality is incomplete. Here, we present results on the physiological response of young Norway spruce trees exposed to lethal drought stress. We applied three levels of drought treatment (control, drying–rewetting, complete drought) and monitored relevant physiological functions and processes of carbon and water relations at high temporal resolution until tree death occurred. Only trees subjected to continuous drought died in our experiment. Trees subjected to drying–rewetting cycles consistently recovered in their ability to transport water, indicating that these trees do not suffer permanent damage to the hydraulic system. In all cases, drought reduced carbon assimilation, caused changes in carbon allocation and appeared to have severely reduced phloem functioning and carbon translocation. Structural growth was sacrificed for carbon investment in maintenance respiration and osmoprotection. Severe drought caused trees to rely on stored carbon reserves but, in contrast to above‐ground tissues, only root carbon pools were strongly reduced when trees died. Our results indicate that drought‐induced changes in carbon allocation, use and transport differ between above‐ and below‐ground tissues in trees. While root death may have been caused by carbon depletion, this was definitely not the case in above‐ground tissues. Our findings indicate that mortality mechanisms are not defined at the organism level but rather within tree compartments.